2014
DOI: 10.1155/2014/536896
|View full text |Cite
|
Sign up to set email alerts
|

Does Polycystic Ovary Syndrome Itself Have Additional Effect on Apelin Levels?

Abstract: Objective. The present study was designed to compare serum levels of apelin between lean PCOS women and healthy women with regular menses. Study Design. A total of 30 lean patients with PCOS and 30 healthy subjects were included in this study. Serum apelin levels were compared between groups. Results. Serum apelin levels in lean PCOS patients were not significantly different from the control subjects. Conclusion. Our findings indicate that PCOS itself does not seem to change apelin levels. Further investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In our laboratory, we repeatedly found that apelin concentration in follicular fluid and levels of apelin and its receptor APJ mRNA in granulosa cells are higher in PCOS patients than in healthy controls [52] (Figure 11). More conflicting data are, however, available for circulating apelin in PCOS women, with an almost equal number of authors reporting significantly lower [128,129,217], higher [196,218] or unchanged [216,219] levels compared to control women (Figure 11).…”
Section: Adipokines and Female Reproductive Pathologiesmentioning
confidence: 99%
“…In our laboratory, we repeatedly found that apelin concentration in follicular fluid and levels of apelin and its receptor APJ mRNA in granulosa cells are higher in PCOS patients than in healthy controls [52] (Figure 11). More conflicting data are, however, available for circulating apelin in PCOS women, with an almost equal number of authors reporting significantly lower [128,129,217], higher [196,218] or unchanged [216,219] levels compared to control women (Figure 11).…”
Section: Adipokines and Female Reproductive Pathologiesmentioning
confidence: 99%
“…Altinkaya et al suggested that serum Apelin levels are lower in women with PCOS than in controls 32 . However, BenkSilfeler et al concluded that serum Apelin levels in lean PCOS patients were not significantly different from the control subjects 33 . In the current study, however, serum Apelin levels are significantly higher in PCOS women compared with controls.…”
Section: %-Specificity %mentioning
confidence: 95%
“…Apelin levels were higher in nonobese PCOS patients, suggesting a compensatory mechanism for metabolic consequences of insulin resistance. Comparative results of studies showing lower serum apelin levels in PCOS have been obtained by several authors [ 73 76 ]. Different from Cekmez et al's study [ 69 ], lower serum concentrations of apelin were found in PCOS subjects by Altinkaya et al [ 75 ] with a positive correlation with BMI, insulin, HOMA-IR, triglyceride, and free testosterone, speculating that apelin can be used as a marker for insulin sensitivity.…”
Section: Physiology and Pathology Of Apelin In The Ovarymentioning
confidence: 99%